The January 2025 Southern California Wildfires: Public Mental Health Impacts and a Call to Action - Marthoenis (Asian Journal of Public Health and Nursing, 2024)
AbstractThe January 2025 Southern California wildfires, among the most severe in recent years, devastated over 40,000 acres, displacing thousands and causing extensive physical and emotional tolls. Beyond the evident physical and economic impacts, the mental health consequences demand urgent attention. This editorial highlights the psychological repercussions, including acute stress, PTSD, anxiety, depression, and substance use disorders, affecting survivors, first responders, and vulnerable populations such as children, the elderly, and low-income communities. Prolonged disruptions and repeated wildfire exposures exacerbate these challenges. The editorial emphasizes the necessity of integrating mental health into disaster response and preparedness strategies, advocating for immediate mental health support, long-term care, and resilience-building within communities. By recognizing mental health as a vital component of disaster management and linking it to climate change policies, a comprehensive approach can mitigate the mental health burden of wildfires and enhance societal resilience to future climate-related disasters.